Influence of Product, Promotion, And Store Atmosphere on Repurchase Intention at Sessama Coffee Shop in Pontianak City With Customer Satisfaction as An Intervening Variable - Agustin, Devi; Fachri, Helman (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of product quality, promotional strategies, and store atmosphere on repurchase intention at Sessama Coffee Shop in Pontianak City, with customer satisfaction as an intervening variable. Using a quantitative associative approach, data were collected from 100 respondents who met specific criteria through purposive sampling. The primary data was analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results showed that product quality, promotional strategies, and store atmosphere significantly influence repurchase intention both directly and indirectly through customer satisfaction. Among these factors, store atmosphere had the most substantial impact on customer satisfaction, highlighting the importance of creating a comfortable and engaging environment. Promotional strategies exhibited the strongest direct effect on repurchase intention, suggesting the critical role of effective marketing in fostering customer loyalty. The mediation analysis confirmed that customer satisfaction plays a pivotal role in amplifying the effects of the independent variables on repurchase intention. These findings emphasize the importance of integrating quality, marketing, and environmental strategies to enhance consumer experiences and drive loyalty. This study provides valuable insights for business practitioners to develop holistic approaches for customer retention and contributes to the understanding of consumer behavior in the retail and service sectors